The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1590/1980-5373-mr-2018-0094
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the Supercapacitive and Superparamagnetic Performances of Iron Oxide Nanoparticles through Yttrium Cations Electro-chemical Doping

Abstract: A one-pot electrosynthesis platform is reported for fabrication of Y 3+ doped iron oxide nanoparticles (Y-IONPs). In this procedure, Y-IONPs are electro-deposited from an additive-free aqueous solution of iron(III) nitrate, iron(II) chloride and yttrium chloride. The analysis data provided by X-ray diffraction (XRD), field emission electron microscopy (FE-SEM) and energy-dispersive X-ray (EDX) confirmed that the deposited Y-IONPs sample is composed of magnetite nanoparticles (size≈20nm) doped with about 10wt% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 56 publications
1
8
0
Order By: Relevance
“…To study the effect of the functionalization process on the crystal structure of Fe 3 O 4 nanoparticles, XRD analysis was performed on the powders, the results were displayed in Figure 5(b). The diffractogram of pristine Fe 3 O 4 NPs shows characteristic peaks at 18.24 o , 30.18 o , 35.54 o , 43.17 o , 57.08 o , 62.67 o corresponding to (220), (311), (400), (511), and (440), respectively, indicating a cubic crystal system belonging to Fd3m (227) space group (COD ID 9005839 46 ) in accordance with the literature 45,47–49 . The XRD pattern for the modified NPs showed the same peaks as with pristine Fe 3 O 4 suggesting that there was no significant change in the materials crystal structure once modified.…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…To study the effect of the functionalization process on the crystal structure of Fe 3 O 4 nanoparticles, XRD analysis was performed on the powders, the results were displayed in Figure 5(b). The diffractogram of pristine Fe 3 O 4 NPs shows characteristic peaks at 18.24 o , 30.18 o , 35.54 o , 43.17 o , 57.08 o , 62.67 o corresponding to (220), (311), (400), (511), and (440), respectively, indicating a cubic crystal system belonging to Fd3m (227) space group (COD ID 9005839 46 ) in accordance with the literature 45,47–49 . The XRD pattern for the modified NPs showed the same peaks as with pristine Fe 3 O 4 suggesting that there was no significant change in the materials crystal structure once modified.…”
Section: Resultssupporting
confidence: 82%
“…45 To study the effect of the functionalization process on the crystal structure of Fe 3 O 4 nanoparticles, XRD analysis was performed on the powders, the results were displayed in Figure 5 46 ) in accordance with the literature. 45,[47][48][49] The XRD pattern for the modified NPs showed the same peaks as with pristine Fe 3 O 4 suggesting that there was no significant change in the materials crystal structure once modified. The peak intensities for Fe 3 O 4 /GPTMS and Fe 3 O 4 /APTES were slightly less than that of Fe 3 O 4 with slight shifts in the peak locations suggesting possible surface modification but a stable crystal structure.…”
Section: Modification Of Fe 3 O 4 Nanoparticlesmentioning
confidence: 99%
“…Similar observations have been reported in several such doped magnetite studies involving other RE ions. [70,71,77,79,80,82,85,100,105] However, due to the relatively large radius, the d-spacing could be expanded by doping. One such example is Y 3+ doping in Fe 3 O 4 , as shown in Figure 3B.…”
Section: Impact Of Re Doping On Morphological Propertiesmentioning
confidence: 99%
“…Studies involving the modification of lattice parameters and crystallite size have been extensively reported for other RE doped iron oxide nanoparticle systems. [31,70,85] It has been observed that for doping with most of the major RE ions, namely Y 3+ , La 3+ , Dy 3+ , Eu 3+ , Nd 3+ , Sm 3+ , Tb 3+ , [31,70,71,77,84,85,94,99,100] a substantial increase in the particle size has been recorded, excepting a few cases. [76,79,105] For example, for Ce doped Fe 3 O 4 , we have categorically observed a decrease in the particle size after doping (Table 5), [76,79] an observation contrary to those reported with Gd and other major RE doped magnetite particles.…”
Section: Impact Of Re Doping On Morphological Propertiesmentioning
confidence: 99%
“…Metal oxide nanoparticles (NPs) can be excellent modifiers in doping of materials in the development of hybrid supercapacitors 16,17 . Lead iodide NPs (PbI 2 -NPs) have been extensively developed due to their potential technological applications in active matrix flat panel imagers (AMFPI), room temperature ionizing radiation detectors, photo-detectors and photovoltaic cells.…”
Section: Introductionmentioning
confidence: 99%